Human intestinal organoid-derived PDGFRα + mesenchymal stroma enables proliferation and maintenance of LGR4 + epithelial stem cells - JunLong Chen; Shinichiro Horiuchi; So Kuramochi; Tomoyuki Kawasaki; Hayato Kawasumi; Saeko Akiyama; Tomoki Arai; Kenichi Morinaga; Tohru Kimura; Tohru Kiyono; Hidenori Akutsu; Seiichi Ishida; et al. (Stem Cell Research & Therapy, 2024)
Abstract Background Intestinal epithelial cells derived from human pluripotent stem cells (hPSCs) are generally maintained and cultured as organoids in vitro because they do not exhibit adhesion when cultured. However, the three-dimensional structure of organoids makes their use in regenerative medicine and drug discovery difficult. Mesenchymal stromal cells are found near intestinal stem cells in vivo and provide trophic factors to regulate stem cell maintenance and proliferation, such as BMP inhibitors, WNT, and R-spondin. In this study, we aimed to use mesenchymal stromal cells isolated from hPSC-derived intestinal organoids to establish an in vitro culture system that enables stable proliferation and maintenance of hPSC-derived intestinal epithelial cells in adhesion culture. Methods We established an isolation protocol for intestinal epithelial cells and mesenchymal stromal cells from hPSCs-derived intestinal organoids and a co-culture system for these cells. We then evaluated the intestinal epithelial cells and mesenchymal stromal cells' morphology, proliferative capacity, chromosomal stability, tumorigenicity, and gene expression profiles. We also evaluated the usefulness of the cells for pharmacokinetic and toxicity studies. Results The proliferating intestinal epithelial cells exhibited a columnar form, microvilli and glycocalyx formation, cell polarity, and expression of drug-metabolizing enzymes and transporters. The intestinal epithelial cells also showed barrier function, transporter activity, and drug-metabolizing capacity. Notably, small intestinal epithelial stem cells cannot be cultured in adherent culture without mesenchymal stromal cells and cannot replaced by other feeder cells. Organoid-derived mesenchymal stromal cells resemble the trophocytes essential for maintaining small intestinal epithelial stem cells and play a crucial role in adherent culture. Conclusions The high proliferative expansion, productivity, and functionality of hPSC-derived intestinal epithelial cells may have potential applications in pharmacokinetic and toxicity studies and regenerative medicine.